(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
This article explores the introduction and development trends of the Authorized Economic Operator (AEO) institution. AEO programs are pivotal in enhancing global trade security and facilitating international supply chain efficiency. The study examines the evolution of AEO standards, their impact on customs processes, and the benefits for businesses, including reduced customs inspections and expedited cargo release. By analyzing current trends and future prospects, the article provides insights into the strategic importance of AEOs in fostering secure and efficient global trade.